Phenomenological study of tacit aesthetics in Merawit Batik and geographical indication certification - Komarudin Kudiya; Saftiyaningsih Ken Atik; Heri Kismo (Universitas Dian Nuswantoro, 2025)
This study examines the tacit aesthetics of Cirebon's Batik Tulis Merawit and its relevance to Geographical Indication certification. The main focus of the study is to understand how bodily experience, visual intuition, and implicit knowledge of the artisans shape the visual character of batik that is distinctive, authentic, and rooted in local traditions. This study uses a qualitative approach with a hermeneutic phenomenology method. Data were collected through participatory observation, in-depth interviews, and visual documentation of the batik practices of Cirebon's Batik Tulis Merawit artisans. Analysis was conducted interpretively to read the relationship between the body, materials, techniques, experiences, and aesthetic meaning. The results show that the aesthetics of Batik Tulis Merawit are not only determined by motifs, colors, or visual forms, but also by the artisans' embodied experiences in processing canting, wax, cloth, hand pressure, line rhythm, ornament density, and color composition. This aesthetic knowledge is tacit because it is passed down through repeated practice, observation, community correction, motor memory, and sensitivity that is difficult to formalize in technical instructions. The findings also indicate that Geographical Indication certification still tends to emphasize aspects of origin, materials, techniques, and the final form of the product, thus not fully accommodating the aesthetic experience of artisans. This study concludes that tacit aesthetics need to be recognized as an important basis for protecting, documenting, and strengthening the quality of Cirebon Batik Tulis Merawit. The practical implication is the need to reformulate Geographical Indication documents to include embodied knowledge, the authority of artisan communities, and local aesthetic standards.